Preclinical NCI-MPACT: prospective modeling of the mutation-based NCI-MPACT clinical trial therapeutic strategy in patient-derived xenograft models - Evrard, Yvonne A.; Alcoser, Sergio Y.; Mullendore, Michael; Chen, Li; Lih, Chih-Jian; Kannan, Vishnuprabha Rahul; Datta, Vivekananda; Dutko, Lindsay; Jiwani, Shahanawaz; Rubinstein, Lawrence V.; Zhao, Yingdong; Williams, P. Mickey; et al. (Frontiers in Oncology, 2025)
PurposeThe National Cancer Institute’s Molecular Profiling-Based Assignment of Cancer Therapy (NCI-MPACT) randomized phase 2 clinical trial assessed the utility of applying tumor DNA sequencing to treatment selection. Here, we report the results of a companion preclinical study in patient-derived xenograft (PDX) models to evaluate how each tumor responded to each of the treatment regimens studied in the NCI-MPACT trial instead of simply to the specific regimen targeting the study-actionable mutation of interest (aMOI).MethodsFifty-one PDX models (46 with and 5 without NCI-MPACT aMOIs) were tested against both the arm that would have been assigned in the NCI-MPACT trial as well as every other study regimen: (1) veliparib plus temozolomide or (2) adavosertib plus carboplatin (targeting the DNA repair pathway); (3) everolimus (targeting the PI3K pathway); and (4) trametinib (targeting the RAS/RAF/MEK pathway). Durability of response was measured by relative median time to tumor quadrupling event-free survival (EFSx4 ≥ 2), and duration of tumor regression.ResultsEleven of 50 models (22%) treated with veliparib plus temozolomide responded according to one or both metrics, as did 2/47 models (4.2%) treated with adavosertib plus carboplatin, and 2/46 models (4.3%) treated with trametinib; no models responded to everolimus. Follow-up studies demonstrated that temozolomide drove the activity of the veliparib plus temozolomide combination and drug sensitivity to temozolomide correlated with MGMT deficiency.ConclusionThis prospective preclinical study confirmed the modest response rates in the NCI-MPACT clinical trial. Substantial responses to temozolomide suggest that this drug represents an effective treatment for patients with MGMT deficiency, regardless of cancer type.